Islamic Republic of Mauritania : Staff Monitored Program. (IMF Staff Country Reports; Country Report ;, 2006)
The Mauritanian transition authorities embarked on a path toward democracy, rule of law, and good governance. The transition authorities initiated a wide range of structural reforms based on the priorities that emerged from consultations with civil society and political parties, and emphasizing the need to improve transparency and governance. The discussions on fiscal and monetary policies and on structural reforms aimed at consolidating recent progress toward macroeconomic stabilization, good governance, and transparency. Mauritania will benefit from considerable technical assistance (TA) from the IMF.